Physical and Chemical Properties of Instant Porridge with Added Moringa Leaf Flour - Zakaria, Zakaria; Rauf, Suriani; Sirajuddin, Sirajuddin; Salim, Andi; Bohari, Bohari (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Moringa leaves are rich in macro and micronutrients; it is expected to produce weaning food that meets nutritional needs. This study aimed to produce an instant porridge formula that meets the terms and conditions of weaning food, including physical characteristics and nutrient contents. Methods: This study employed a completely randomized design experiment with three replications to evaluate the impact of moringa leaf flour (0, 5, 7.5, and 10 g/recipe) on infant weaning food prepared from soybeans and wheat. Soybean and moringa leaf flours were prepared following established protocols. Instant porridge production involved mixing, baking, drying, and grinding, followed by density and water absorption analysis using standard methods. Nutritional content was analyzed by a certified laboratory. Descriptive statistics and data visualization will be used to present the findings. Results: Formula F1 (5 g) has a preference category above 88% of panelists who accepted it based on aspects of color, texture, aroma, and taste. The average density of instant porridge is 0.53 g/ml, and the water absorption capacity is 1.74 ml/g. The nutritional content per 100 g of energy is 471 Kcal, protein 19.7 g, total fat 19.7 g, linolenic fatty acid 464 mg, total carbohydrates 54.7 g, sucrose 21.24 g, water content 3.5 g, iron 44.6 g, and calcium 117.2 mg. Conclusion: The instant porridge produced meets the essential physical characteristics required for infant weaning foods. Additionally, its nutritional profile, except for total fat, satisfies the energy and nutrient needs for infants aged 6-11 months.